1998
DOI: 10.1108/08858629810222225
|View full text |Cite
|
Sign up to set email alerts
|

Interorganizational information system technology and buyer‐seller relationships

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 37 publications
1
68
0
1
Order By: Relevance
“…Partnership satisfaction can be defined as how well the result of partnership meets the expectation of the participants [9,15,16]. The quality of service provided by the partner viewed as a result of the partnership.…”
Section: Partnership Satisfactionmentioning
confidence: 99%
“…Partnership satisfaction can be defined as how well the result of partnership meets the expectation of the participants [9,15,16]. The quality of service provided by the partner viewed as a result of the partnership.…”
Section: Partnership Satisfactionmentioning
confidence: 99%
“…The fourth group studied the benefits/values of IOC, including cost reductions through increased channel efficiency, product quality improvement, as well as strategic benefits by developing and maintaining market position (Wilson and Vlosky, 1998). It is reported that information sharing improves the performance of both actors and chains (Mahmoudi et al, 2007).…”
mentioning
confidence: 99%
“…On the one hand, they should be aware of their customers' demands, requirements and expectations, so as to service their customers' needs better (market-oriented theory) and avoid potential risks. On the other hand, they should also present their own business and requirements to their suppliers and help them understand properly in order to get a better service from their suppliers (Wilson and Vlosky, 1998). To distinguish these two types of communication quality, we formulated two constructs to test in the model, including (regular) 'information quality' and 'knowledge on business partners' (changing) requirements and expectations' .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Commitment was measured using three items that captured the attitudinal and temporal components of commitment (Kumar et al 1995, Wilson andVlosky 1998). Relational norms were measured using eight items that measured four norms most frequently used to operationalise the construct of relationalism.…”
Section: Measures Usedmentioning
confidence: 99%